Kalām Khabar (Informative Sentence) In Mudzakarāt Ṭabībah Works of Nawal El Sa'dāwi (Pragmatic Analysis) - Mirza Mahbub Wijaya; Cici Andriyani (JURNAL IJ-ATL, 2021)
This study is a literature research that discusses the kalām khabar in the Mudzakarāt Tabībah novel. Furthermore, the author uses the technical distribution data analysis method for direct elements by presenting the data using a random sample because there are too many kalām khabar found. From 100 data as samples, researchers found 68 kalām khabar which did not experience deviations and 38 kalām khabar which experienced deviations. Kalām khabar which has no deviation is 62 kalām khabar ibtidāi (with details of 14 ibtidāi for al-istirhām, 10 ibtidāi for iẓhārut-da'fi, 6 ibtidāi for iẓhārut-tahassur, 4 ibtidāi for al-fakhr, and 27 ibtidāi to encourage efforts and diligent), 1 kalām khabar aims at iẓhārut-da'fi, 2 kalām khabar ṭalabī (aims to encourage and be diligent), 2 kalām khabar inkāri (aim at iẓhārut-da'fi and aim at iẓhārut-tahassur). Whereas kalām khabar which has deviations, namely 2 kalām khabar ibtidāi-ṭalabī aims for iẓhārut-da'fi, 2 kalām khabar ibtidāi-ṭalabī aims to urge to try and be diligent, 1 kalām khabar ibtidāi-inkārī aims to istirhām, 1 kalām khabar ibtārām aims at istirhām, 1 kalām khabar ibtidāi-inkārī khabar ibtāruthām, 1 kalām khabar ibtārutām -tahassur, 1 kalām khabar ṭalabī-ibtidāi aims at istirhām, 3 kalām khabar ṭalabī-ibtidāi aims ṭalabrut-ibtidāy tries khabar ṭalabī-inkārī aims at istirhām, 1 kalām khabar inkārī-ibtidāi aims at iẓhārut-da'fi, 1 kalām khabar inkārī-ibtidāi aims at iẓhārut-tahassur, 1 kalām khabar inkārī-ibtidām aims to encourage inkārī-ibtidām khabar inkārī-ibtidām